PERAN GURU DALAM MENANGANI PERILAKU BULLYING PADA SISWA KELAS VI SDN 242 BALUBUE KABUPATEN SOPPENG - Karnaini; Sangkung Panggalo, Iindarda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of teachers in handling bullying behavior and to identify the challenges faced by teachers among sixth-grade students at SDN 242 Balubue, Soppeng Regency. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews with the sixth-grade homeroom teacher and the school principal, observations of teacher activities and student interactions, and relevant documentation. Data were analyzed using the Miles, Huberman, and Saldaña model through data condensation, data display, and conclusion drawing and verification. The findings show that the teacher plays several roles in handling bullying behavior, namely as an educator, counselor, role model, supervisor, and mediator. These roles are implemented through education on respectful behavior, student guidance and support, positive modeling, supervision of student interactions, and persuasive conflict resolution. Observations showed that student interactions were generally conducive, with no students observed to be socially excluded, although occasional teasing occurred in the context of joking. The challenges faced by the teacher included limited time, students' reluctance to report bullying, difficulties in collaborating with some parents, and limited monitoring of students' digital interactions outside school. These findings indicate that addressing bullying in elementary schools requires consistent teacher involvement as well as support from the school and family.